Analisis Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Online Travel Agent (Traveloka, Tiket.Com, Agoda, Dan Pegi-Pegi) - Yunita Indriany; Nika Sintesa; Darmawan Darmawan (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine and analyze the effect of Promotion and Service Quality on Consumer Satisfaction, either partially or simultaneously on the Online Travel Agent (Case Study of Traveloka, Tiket.com, Agoda, Pegi-pegi Customers). The type of research used is a quantitative approach. The sampling technique used was purposive sampling method, namely the data was selected based on certain criteria.. The data analysis method used was multiple linear regression analysis (SPSS). The results of this study indicate that: (1) Promotion (X1) partially has a positive and significant effect on consumer satisfaction as evidenced by the results of a significance t of 0.116; (2) Service Quality (X2) partially does not have a Positive and Significant effect on Consumer Satisfaction, this is evidenced by the results of a significance t of 0.000; Simultaneous promotion, and service quality have a significant effect on consumer satisfaction as evidenced by the results of a significance F of 0.000 which is smaller than 0.05.Keywords: Consumer Satisfaction, Promotion, Service Quality